Exploring the Nation: Gender, Identity and Cuisine in the UAE - Khansaheb, Ayisha (Hawwa, 2021)
Abstract This article examines various heritage displays and festivals that have occurred in the United Arab Emirates and analyzes, in particular, the representation of women and cuisine. Over a two-year period (August 2015 to August 2017), I interviewed senior Emirati women and collected their oral histories, focusing mainly on cooking practices in the past and how those practices evolved with time. The article compares those oral histories with the representations shown in heritage festivals and spaces and concludes that the women I interviewed are inadequately represented and that the presentation of women, along with the culinary traditions in the region, has been marginalized or oversimplified.